Thai Undergraduate Students’ Initial Perceptions of Learning English through Duolingo - White, Alan; Jaroenchaiwat, Piyawan; Detdamrongpreecha, Busarin; Pipattarasakul, Piyarat (RMUTK Journal of Liberal Arts, 2024)
This study examined Thai undergraduate students' initial perceptions of using Duolingo to learn English. The samples of this study were 25 Thai 3rd year undergraduate Japanese major students. The samples were taking English as a minor subject. The samples were chosen as they were readily available and possessed the necessary attributes for this study. Twenty-four out of twenty-five students had never used Duolingo previously, and one student had used the application for less than one week. The students were therefore deemed to be unfamiliar with the application. The study used a 5-point Likert scale questionnaire and closed-end interview questions. The results of this study showed that students were generally favourable toward the Duolingo application. However, issues were noted concerning advertising and the rewarding system.